Storey's Guide to Raising Rabbits : Breeds, Care, Housing - Bennett, Bob, 1936-; Bennett, Bob, 1936- (North Adams, MA : Storey Publishing, 2018)
"This comprehensive guide offers expert advice on breed selection, housing, feeding, humane handling, and more"--Amazon.com.
Getting started -- Housing, feeding, and breeding -- Marketing and miscellany.
Includes bibliographical references (page 210) and index.
Keywords: Rabbits; Rabbits -- Breeding; Rabbit breeds; Rabbits -- Feeding and feeds